Peningkatan Kapasitas Umkm Melalui Program Pelatihan Manajemen Dan Pemasaran Di Desa Partoruan Lumban Lobu - Mhd Gifari Sitorus; Rasta Kurniawati Br Pinem (Yayasan Salam Cerdas Al-Fattah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving the local economy, particularly in rural areas such as Partoruan Lumban Lobu Village. However, limited managerial capabilities and inadequate marketing strategies often become major obstacles for MSME actors in improving their competitiveness and productivity. This study aims to analyze the effectiveness of management and marketing training programs in enhancing the capacity of MSME entrepreneurs in the village. The research method employs a qualitative approach with observation, interview, and documentation techniques. The results show that after participating in the training, MSME actors experienced significant improvements in financial management, promotional strategies, and the use of digital media as a marketing tool. The training program also increased the entrepreneurs’ awareness of the importance of innovation and collaboration among MSME players to expand their business networks. Thus, management and marketing training proved effective in strengthening the capacity of MSMEs at the village level.